Chasing the Ghost: Hyperinflammation Does Not Cause Sepsis - Shapiro, Leland; Scherger, Sias; Franco-Paredes, Carlos; Gharamti, Amal A.; Fraulino, David; Henao-Martinez, Andrés F. (Frontiers in Pharmacology, 2022)
Abstract (326 words) Corona virus disease 2019 (COVID-19), or disease following infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an example of sepsis. Sepsis is infection sufficient to cause illness in the infected host, and more severe forms of sepsis can result in organ malfunction or death. Following infection, excessive inflammation generated in the infected host, also referred to as a cytokine storm, is thought to be the essential cause of illness, organ malfunction, or death. Since COVID-19 is an example of sepsis, the hyperinflammation concept has influenced scientific investigation and treatment approaches to COVID-19. However, decades of laboratory study and more than 100 clinical trials designed to quell inflammation have failed to reduce sepsis mortality. We examine the theoretical support underlying belief hyperinflammation or cytokine storm causes sepsis. Our analysis shows remarkable weakness of the hyperinflammation concept of sepsis that includes conceptual confusion and failure to establish a cause-and-effect relationship between hyperinflammation and sepsis. We conclude anti-inflammation approaches to sepsis therapy have little chance of future success. Therefore, anti-inflammation approaches to treat COVID-19 are likewise at high risk for failure. We find persistence of the cytokine storm concept in sepsis perplexing. Although all sepsis treatment approaches based on the hyperinflammation concept of pathogenesis have failed, the concept has shown remarkable resilience and appears to be unfalsifiable. A novel approach to understanding this resilience is to consider the hyperinflammation or cytokine storm concept as an example of a scientific paradigm. Thomas Kuhn developed the idea that paradigms generate rules of investigation that both shape and restrict scientific progress. Intrinsic features of scientific paradigms include resistance to falsification in the face of contradictory data, and inability of experimentation to generate alternatives to a failing paradigm. We call for rejection of the concept that hyperinflammation or cytokine storm causes sepsis. Using the hyperinflammation or cytokine storm paradigm to guide COVID-19 treatments is likewise unlikely to provide progress. Resources should be redirected to more promising avenues of investigation and treatment.